2011
DOI: 10.1113/jphysiol.2011.207902
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide regulation of colonic epithelial ion transport: a novel role for enteric glia in the myenteric plexus

Abstract: Non-technical summary The enteric nervous system of the gastrointestinal tract regulates all the functions of the gut. Enteric neurons are surrounded and outnumbered by enteric glial cells, whose functions are not well understood. Digestive and defensive functions of the gut require the secretion of fluid into the lumen in a regulated manner. Fluid is controlled by the secretion or absorption of ions across the epithelium. Here we have identified a physiological role for enteric glia of the colon in the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 55 publications
1
61
1
Order By: Relevance
“…The EGCs network has trophic and protective functions toward enteric neurons and is fully implicated in the integration and the modulation of neuronal activities [33][34][35] . In addition, EGCs within the ENS have a significant role in forming a diffusion barrier around the capillaries surrounding ganglia similar to that of bloodbrain barrier [3,15,[36][37][38] . Interstitial cells of Cajal (ICCs) are also related to the ENS and are electrically coupled to the smooth muscle cells.…”
Section: Non-neuronal Cells In the Ensmentioning
confidence: 99%
See 1 more Smart Citation
“…The EGCs network has trophic and protective functions toward enteric neurons and is fully implicated in the integration and the modulation of neuronal activities [33][34][35] . In addition, EGCs within the ENS have a significant role in forming a diffusion barrier around the capillaries surrounding ganglia similar to that of bloodbrain barrier [3,15,[36][37][38] . Interstitial cells of Cajal (ICCs) are also related to the ENS and are electrically coupled to the smooth muscle cells.…”
Section: Non-neuronal Cells In the Ensmentioning
confidence: 99%
“…The secretion of glia cell-derived neurotrophic factor (GDNF), nerve growth factor (NGF) and transforming growth factor-beta contribute to the maintenance of endothelial integrity and vasodilatation [82] . Evidence is accumulating that EGCs share the ability of astrocytes to regulate tight-junction integrity and cellular interactions comparable with those maintaining the blood-brain barrier and creating the proper microenvironment for enteric neurons [36,38] . To know the exact mechanisms of how EGCs contribute to gut homeostasis under physiological and pathophysiological conditions is therefore important to work out new therapeutic strategies and to be aware of diabetes-related vascular complications.…”
Section: Enteric Gliamentioning
confidence: 99%
“…The presence of cytokine receptors on enteric glia is a very interesting feature of this study and should be confirmed with additional experimental approaches. Enteric glia may also contribute to ileus through the production of NO from iNOS (37,38), though this has yet to be directly demonstrated.…”
Section: Role Of Enteric Glia In Gi Motility Disordersmentioning
confidence: 99%
“…The high density of NOS-containing neurons in the young ileum is believed to contribute to this result . Recently, it has been suggested that NO release from neurons and enteric glia can be triggered by nicotinic signaling to regulate epithelial ion transport in segments of mouse colon (MacEachern et al , 2011 ).…”
Section: Neuronal Mediation In the Gastrointestinal Tractmentioning
confidence: 99%
“…Similarly, modified platinum microelectrodes can also be used (Shin et al , 2008 ;Park et al , 2009 ). Other forms of carbon materials have been investigated, including nanotubes and nanoparticles Porras Gutierrez et al , 2009 ;Deng et al , 2010 ;Xu et al , 2011 ;Chng and Pumera , 2012 ), graphene and nanosheets of graphite (Wu et al , 2010 ;Ng et al , 2011 ;Chng and Pumera , 2012 ), and boron-doped diamond (BDD) electrodes (Patel et al , 2008bMacEachern et al , 2011 ). Microfabrication has also been extensively used to produce NO sensors in the form of microelectrode arrays Chang et al , 2005 ;Patel et al , 2008a ;Trouillon et al , 2010aTrouillon et al , , 2012Quinton et al , 2011 ) or microfluidic systems with integrated electrochemical detection Cha et al , 2010 ;Gunasekara et al , 2012 ).…”
Section: Introduction: Biological Role Of Nitric Oxidementioning
confidence: 99%